Influence of Living Sunnah on Customers Satisfaction Basmalah Store Malang with Service Quality as Moderating Variables - Safitri, Wulan Nur; Aliyah, Faizatul; Rofiq, Aunur (Perkumpulan Dosen Program Hibah Indonesia, 2023)
One way to increase Customers Satisfaction is by applying the